A low profile wideband horizontally polarized omnidirectional printed loop antenna. Issue 2 (17th November 2021) - Li, Xudong; Ren, Yuhui; Wu, Handong; Cui, Feng; Li, Ke; Wang, Fuwei
Abstract: This article presents a low profile horizontally polarized omnidirectional antenna in S ‐band. The antenna adopts a printed coupling loop structure which consists of an inner ring radiator, an outer ring radiator and an 8‐channel power divider. The inner ring radiator is composed of eight symmetrical arc‐shaped branches, which are excited by power divider with constant amplitude and phase. Hence, these branches produce a uniform current in the same circumferential direction. The bandwidth of the antenna is broadened by loading an outer ring radiator which is feed by energy coupling. The outer ring is also divided into eight segments to ensure the same current direction as the inner ring. Measured results show that the frequency range for | S 11 | < −10 dB is from 2.17 to 2.86 GHz (27.4%), and the gain variation in azimuthal angle is less than 2.7 dB in the same band. Meanwhile, the height of the antenna is only 0.025 λ 0 .